BIOMASS AND ESSENTIAL OIL PROCUCTION OF CHAMOMILE CULTIVATED WITH DIFFERENT LEVELS OF POULTRY LITTER - NALEPA, Thiago; CARVALHO, Ruy Inacio Neiva de (Scientia Agraria, 2007)
The experiment was carried out Campo Magro, Parana State, Brazil, from March to November, 2006. The objective was to evaluate the essential oil production of chamomille cv. Mandirituba and the variations in the vegetative and reproductive growth after the organic fertilization with different doses of poultry litter (0; 2,5; 5,0; 7,5; 10,0 e 12,5 kg m-2). The experimental design was the randomised block with six treatments and four replications, and each parcel has a total area of 6 m2 (2 x 3 m) and an useful area of 2 m2. The height of plants was measured in each parcel; the highest plants (60,9 cm) were obtained after the fertilization with an estimated dose of 10,3 kg m-2. The average average production of fresh and dried matter of capitula presented a direct relation with the increase of the doses used and the production of essential oil in capitula was not influenced by the fertilization. The average yield of essential oil was 6,56 L ha-1 with the dose of 12,5 kg m-2. The highest production of capitula fresh mass was 2.483,7 kg ha-1 and the dried mass was 471,8 kg ha-1 after the fertilization with 12,5 kg ha-1 of poultry litter.